PENGARUH PENGETAHUAN KEUANGAN, KEPERCAYAAN, PERILAKU KONSUMTIF TERHADAP KEPUTUSAN MENABUNG GENERASI Z KABUPATEN TULUNGAGUNG - Rima Fitriasari; Eko Purwanto (Universitas Islam Kadiri, 2021)
The development of a country can be seen from the economic development in a country, especially Indonesia, it can be seen from the amount of funds owned. The culture of saving in Indonesian society is currently known to be quite low compared to other Asian countries. This is reflected in the low desire to save. Savings is one of the important factors in the economy in a country, because the economy will be strong if the country has a high level of savings. Savings are used as a precaution in the face of something that might happen in the future.This study aims to analyze the effect of financial knowledge, trust, consumptive behavior on saving decisions. The population in this study was Generation Z, Tulungagung Regency. The sampling technique in this study used purposive sampling technique. The technique of determining the number of samples using the slovin formula. The sample used in the study was 100 people or respondents. The data used in this study is primary data which is data from the questionnaire results from the answers of 100 respondents. The analysis technique in this study uses Partial Least Square (PLS).The results of the study indicate that financial knowledge, trust, and consumptive behavior have a significant positive influence on saving decisions.